The Artistic Features of Roman Sculpture in the Imperial Era (Journal of the College of Basic Education, 2026)
This research explores one of the key phases in the development of Roman sculpture, spanning from the reign of Augustus to the fall of the Western Roman Empire. It addresses general classifications and the artistic features of sculpture, focusing on compositional elements. The second chapter offers a general yet detailed overview through two sections: the first discusses topics such as Greek influence on Roman sculpture, Roman plundering of Greek art, and the Roman approach to sculpture. The second section explores the replication of Greek works, sculptors, and common themes. The third chapter presents a sample of sculptures for analysis, leading to conclusions such as: the diversity of Roman sculpture's purposes—political, religious, funerary, and propagandistic; the integration of sculpture with architecture; the use of varying levels of relief depending on function (high and low relief); and the dominance of a closed, structured compositional style, among other findings.